2015
DOI: 10.1002/dc.23365
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Langerhans cell histiocytosis with prominent eosinophilic emperipolesis

Abstract: Multinucleated giant cells of osteoclastic type are known to occur in nodal and extranodal lesions of Langerhans cell histiocytosis (LCH). These giant cells are thought to be derived from phagocytic histiocytes, which correlate with the degree of necrosis in LCH lesions. Emperipolesis commonly seen in Rosai-Dorfman disease is a distinct phenomenon characterized by intact phagocytosed cells in an intracytoplasmic vacuole protected from proteolytic digestion. We present a case of emperipolesis of inflammatory ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The presence of eosinophils and in conjunction with RDD has been reported in association with idiopathic hypereosinophilic syndrome at autopsy in multiple sites, and in a patient with known RDD who later developed cutaneous lesions . Eosinophilic emperipolesis has been described recently in a case of nodal Langerhans cell histiocytosis . No reports were found documenting the presence of eosinophilic emperipolesis in RDD, which was a constant feature in all of our cases.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The presence of eosinophils and in conjunction with RDD has been reported in association with idiopathic hypereosinophilic syndrome at autopsy in multiple sites, and in a patient with known RDD who later developed cutaneous lesions . Eosinophilic emperipolesis has been described recently in a case of nodal Langerhans cell histiocytosis . No reports were found documenting the presence of eosinophilic emperipolesis in RDD, which was a constant feature in all of our cases.…”
Section: Discussionsupporting
confidence: 56%
“…25 Eosinophilic emperipolesis has been described recently in a case of nodal Langerhans cell histiocytosis. 26 No reports were found documenting the presence of eosinophilic emperipolesis in RDD, which was a constant feature in all of our cases. This appears to be a unique finding in this context.…”
Section: Discussionmentioning
confidence: 59%
“…In rare cases of RDD, nuclear atypia, eosinophil infiltrate, and patients synchronously diagnosed with CHL were reported. [16][17][18] Nevertheless, to the best of our knowledge no study has specifically reported CD30 expression in RDD cells. BRAF V600E mutations were described in various histiocytic/dendritic cell lesions, including LCH 6 ; however, they were not found in either of the previous or present patients.…”
Section: Discussionmentioning
confidence: 97%
“…Emperipolesis is commonly observed in RDD, although it is not a prerequisite for the diagnosis. In rare cases of RDD, nuclear atypia, eosinophil infiltrate, and patients synchronously diagnosed with CHL were reported 16–18 . Nevertheless, to the best of our knowledge no study has specifically reported CD30 expression in RDD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is required for the diagnosis of RDD, it is not specific to this condition. Emperipolesis can be observed in various physiological and pathological conditions, including sarcoidosis [22], LCH [23], ECD [24], Hodgkin and non-Hodgkin lymphoma [25,26], neuroblastoma [21,27], epithelioid glioblastoma [28], and others [21].…”
Section: Discussionmentioning
confidence: 99%